Online groups show how technology supports healthcare needs for patients and families: an illustrative model for COPD facebook groups - Boyce, LeAnn; Prybutok, Gayle; Prybutok, Victor (Frontiers in Medical Engineering, 2024)
This study examines how online technologies can support patients and their families address specific medical needs by creating an integrated theoretical framework based on the Health Belief Model, Social Exchange Theory, and Technology Acceptance Model. We obtained a total of 264 responses from an online survey posted in several COPD Facebook groups. After data preprocessing, we were left with 155 responses that met our inclusion criteria. Using the Partial Least Squares-Structural Equation Model (PLS-SEM), we evaluate how individuals in Chronic Obstructive Pulmonary Disease (COPD) Facebook groups seek information. This study examines the relationship between demographic variables, psychological attributes (including emotional support and self-worth), perceived disease severity, benefits and barriers, and the perceived utility and ease of internet use in the information-seeking behavior of COPD patients on Facebook. The findings underscore the importance of ease of internet use and intuitive platform design as a critical determinant that positively affects user engagement and fosters active participation among online participants. These findings offer critical insights into how online communities help patients and families obtain broad support and enhance the adoption and acceptance of emerging healthcare technologies. This also shows the advantages that online platforms offer individuals managing chronic diseases. Given these insights, we urge healthcare providers to recognize the beneficial effects of online health communities on patient well-being and health outcomes. This understanding is essential for healthcare professionals seeking to enhance patient care, aiming to improve the quality of life for individuals with chronic diseases in an increasingly digital landscape.